Ilmu Kesehatan Peningkatan Kesehatan Gigi Dan Mulut Dengan Penurunan Angka Karies Dan Peningkatan Pti Di Madrasah Ibtidaiyah Al Anshor Martapura: Kesehatan Gigi dan Mulut - Rahmawati, Ida; Bin Said, Fahmi; FANSURNA, ANDERI (UPPM Poltekkes Kemenkes Banjarmasin, 2023)
Dental and oral health is one aspect of body health that cannot be ignored, one of which is dental caries. Fluorine contained in water has an impact that can affect dental caries. According to laboratory test reports, Martapura river water in the Kitano River Village area, has a fluorine content of 0.45 ml / l and in the North Kuin region has a fluorine content of 0.0846 mg / l. This community service aims to determine the relationship between counseling, simple treatment with increasing knowledge and increasing PTI in Madrasah Ibtidaiyah AL Anshor Sei Kitano, Banjar Regency, Puskesmas Working Area in Pagar Banjar Regency. The method used is observational analytic with a cross sectional approach. The community service population is grade I to grade VI students at Madrasah Ibtidaiyah AL Anshor Sei Kitano, Banjar Regency, Puskesmas Dalam Pagar Working Area, totaling 104 students. The sampling technique uses Total Sampling. The results of this community service are expected to reduce Dental Caries and increase PTI in Madrasah Ibtidaiyah AL Anshor Sei Kitano, Banjar Regency, Puskesmas Dalam Pagar Working Area. It is recommended to the community, especially parents to pay more attention to the health of their own teeth and mouth as well as the health of their children's teeth and mouth in order to prevent early tooth decay. Keywords: Dental caries, PTI number